2018
DOI: 10.1186/s12909-018-1287-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rural outreach programs on medical students’ future rural intentions and working locations: a systematic review

Abstract: BackgroundSignificant investment has been undertaken by many countries into ‘Rural Clinical Training Placement Schemes’ for medical students in order to deal with shortages of trained health care professionals in rural and remote locations. This systematic review examines the evidence base of rural educational programs within medical education and focusses on workforce intentions and employment outcomes. The study provides a detailed description of the methodological characteristics of the literature, thematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 96 publications
2
98
1
Order By: Relevance
“…Recent dental systematic reviews have outlined the need for greater sophistication in the research design to assess outreach programs and have demanded for large‐scale workforce data, and the use of appropriate statistical techniques to isolate and evaluate potential factors related to rural employment . This study has investigated key potential rural predictors identified in recent medical education rural outreach studies namely; rural background, rural experience and pre‐ and post‐placement rural intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent dental systematic reviews have outlined the need for greater sophistication in the research design to assess outreach programs and have demanded for large‐scale workforce data, and the use of appropriate statistical techniques to isolate and evaluate potential factors related to rural employment . This study has investigated key potential rural predictors identified in recent medical education rural outreach studies namely; rural background, rural experience and pre‐ and post‐placement rural intentions.…”
Section: Discussionmentioning
confidence: 99%
“…reported that rural background can be a strong indicator of future rural practice. In medical education, there is substantial evidence of the influence of rural background on graduates’ future workforce outcomes . Furthermore, two medical education reviews have described rural background as the strongest predictor of rural employment .…”
Section: Discussionmentioning
confidence: 99%
“…This is an issue faced by many medical and dental education programs as it is ethically challenging to make educational interventions mandatory and assign students to certain settings. 17,58,59 It is therefore possible that the RCPP participants had higher pre-placement rural intentions; however, prior research helps to mitigate this potential bias. First, the 2009 student cohort evalua- 18,19 ; thus, pre-placement almost half of the participants did not want to work rurally after graduation.…”
Section: Limitationsmentioning
confidence: 99%
“…One strategy to encourage new graduates to work rurally is through the provision of rural outreach placements during educational training. In medical education, there is considerable evidence for the effectiveness of outreach programs during training, with both Rural Clinical Placement Programs (RCPPs) and Rural Clinical Schools (RCSs) reporting positive associations of graduates with rural employment.…”
Section: Introductionmentioning
confidence: 99%